A 5-year Longitudinal Study of Low Back Pain in Survivors of the Great East Japan Earthquake. Issue 10 (15th May 2021) - Yabe, Yutaka; Hagiwara, Yoshihiro; Sekiguchi, Takuya; Sugawara, Yumi; Tsuchiya, Masahiro; Yoshida, Shinichirou; Sogi, Yasuhito; Onoki, Takahiro; Suzuki, Kazuaki; Takahashi, Tadahisa; Iwatsu, Jun; Tsuji, Ichiro; et al.
Abstract : Study Design: A longitudinal panel study. Objective: The aim of this study was to examine the occurrence of low back pain (LBP), especially the association of previous LBP with further episodes of LBP, in survivors of the Great East Japan Earthquake (GEJE) during the course of 5 years. Summary of Background Data: LBP is common among survivors of natural disasters, but its long-term course is not clear. Methods: A 5-year longitudinal study was conducted among survivors of the GEJE (n = 1821). The presence of LBP was assessed using a self-reported questionnaire at 2, 4, and 7 years after the disaster (termed the first, second, and third time points, respectively). Multiple logistic regression analysis was performed to assess a potential association between LBP at the first and second time points with LBP at the third time point, and the odds ratios (ORs) and 95% confidence intervals (CI) were calculated. Results: The prevalence of LBP was 25.3%, 27.3%, and 27.2% at the first, second, and third time points, respectively. The occurrence of LBP at the first time point was significantly associated with LBP at the third time point, and the adjusted odds ratio (OR) (95% confidence interval [CI]) was 5.47 (4.28–6.98). Furthermore, LBP at the first and second time points was significantly associated with LBP at the third time point. Compared to no LBP at the first and second time points, the adjusted OR (95% CIs) for LBP at the third time point was 4.12 (3.14–5.41) in the case of LBP at either of the first or second time points and 10.73 (7.80–14.76) for LBP at both time points ( P for trend < 0.001). Conclusion: Previous LBP was associated with LBP 5 years later among survivors of the GEJE. Furthermore, the effect on subsequent LBP was stronger with a higher frequency of previous LBP episodes. Level of Evidence: 3